2013
DOI: 10.3390/catal3030709
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Immobilized Organocatalysts for Asymmetric Reactions in Aqueous Media

Abstract: Ionic liquids are organic salts with melting points typically below ambient or reaction temperature. The unique combination of physical properties of ionic liquids, such as lack of measurable vapor pressure, high thermal and chemical stability, make them ideal to be used as reusable homogenous support for catalysts. In addition, the solubility of ionic liquids in various reaction media can be controlled and easily fine-tuned by modification of the structures of their cations and anions. As a result, ionic liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 94 publications
2
15
0
Order By: Relevance
“…These findings fit with the reported data on telomerase activity in gliomas which is considerably higher in GBM (50-89 %) and oligodendrogliomas (75-100 %), than in astrocytomas (0-45 %) [49,67,106]. The low frequency of TERT promoter mutations and telomerase activity in grades II and III astrocytomas can be explained by the high prevalence of ATRX mutations, one of the most frequent mutations in this type of glioma [56]. It is known that ATRX mutations trigger ALT in astrocytoma cells and it has been shown that this alternative mechanism is frequently activated in astrocytomas, allowing telomere maintenance without the need for telomerase reactivation [48].…”
Section: Telomerase Promoter Mutations In Bladder Carcinomassupporting
confidence: 80%
“…These findings fit with the reported data on telomerase activity in gliomas which is considerably higher in GBM (50-89 %) and oligodendrogliomas (75-100 %), than in astrocytomas (0-45 %) [49,67,106]. The low frequency of TERT promoter mutations and telomerase activity in grades II and III astrocytomas can be explained by the high prevalence of ATRX mutations, one of the most frequent mutations in this type of glioma [56]. It is known that ATRX mutations trigger ALT in astrocytoma cells and it has been shown that this alternative mechanism is frequently activated in astrocytomas, allowing telomere maintenance without the need for telomerase reactivation [48].…”
Section: Telomerase Promoter Mutations In Bladder Carcinomassupporting
confidence: 80%
“…The latter possibly resulted from impaired transcription, as RNAP II levels were also severely depressed following ATRX inactivation. Previous findings, mainly from clinical studies, have pointed to the simultaneous occurrence of a mutation in ATRX and of the telomeraseindependent ALT pathway in several types of tumors (10,11,(20)(21)(22)(23). This list is not exhaustive, as other, more recent studies have confirmed these early findings.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, in several clinical studies, mutations in ATRX were found to be tightly associated with the ALT pathway in various types of tumors (10,11,(20)(21)(22)(23). This correlation has also been observed in cultured cells (24,25).…”
Section: Atrx Localizes To Subtelomeric Regions Of Human Glioma Cellsmentioning
confidence: 60%
“…However, the immobilization of organocatalyst to ionic liquid systems gave catalyst which can be used either under organic or aqueous homogeneous conditions [101]. Hence, several functionalized ionic liquids have been attached to the pyrrolidine motif after quaternization of the pyrrolidineimidazole precursor.…”
Section: Aqueous Aldol Reactions With Supported Organocatalystsmentioning
confidence: 99%